Efecto de lufenuron sobre la germinación, el cremiento y la actividad entomopatógena de Lecanicillium lecanii en condiciones de laboratorio - Payano Lopez, Waldo Kenner (2019)
The effect of lufenuron on the germination, growth and entomopathogenic_x000D_ activity of Lecanicillium lecanii was determined and that no significant difference_x000D_ on growth under laboratory conditions. For which we worked with three_x000D_ concentrations of lufenuron (30 ppm, 37.5 ppm, 50 ppm). The germination_x000D_ percentage was determined by adding 2 mL of each dilution (double_x000D_ concentrate) of the chemical to tubes containing 2 mL of standardized spore_x000D_ suspension of L. lecanii, thus obtaining a final solution of 1x105 spores / mL,_x000D_ incubating at 25 ° C for 18 to 24 hours. Then the germinated and non-germinated_x000D_ spore count was performed. The mycelial growth of L. lecanii was evaluated by_x000D_ seeding by puncture in the central area in Petri dishes containing Papa Dextrose_x000D_ Agar with the different concentrations of both Lufenuron, these were incubated_x000D_ at 25 ° C for 10 days, the mycelial growth radius was measured (mm) It was_x000D_ found that lufenuron inhibits up to 100% germination of L. lecanii. In relation to_x000D_ the mycelial growth, lufenuron reduced the growth to a percentage, in the_x000D_ established concentrations it has an inhibitory effect on the germination of L._x000D_ lecanii, while in growth there is no significant inhibitory effect on the growth of_x000D_ the fungus.